Interface structure of high-reliability silicon nitride AMB substrate and preparation method thereof
By using silverless solder paste and vacuum brazing process on the copper-ceramic interface of the silicon nitride AMB substrate, a specific interface structure is formed, which solves the problem of stress concentration and improves the reliability of the module, achieving low cost and high reliability silicon nitride AMB substrate.
Patent Information
- Application Number
- CN202411606602.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing silicon nitride AMB substrates have stress concentration problems at the copper-ceramic interface, resulting in ceramic cracking or copper layer peeling, which in turn affects the reliability of the module. At the same time, the existing silverless solder paste process is costly and difficult to achieve high reliability.
Silver-free solder paste is prepared by mixing metal powder and organic carrier, and after printing solder paste on both sides of silicon nitride ceramic, copper sheets are stacked, vacuum brazing is performed to form a layer of copper-solder paste-ceramic-solder paste-copper Structure, regulates the structural design of the brazing interface to reduce residual stress.
The interface structure of the high-reliability silicon nitride AMB substrate is realized, which significantly improves the stability and temperature reliability of the interface structure, avoids silver migration problems and reduces costs.
Smart Images

Figure CN119517748A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of semiconductor substrate preparation, and in particular to an interface structure of a high-reliability silicon nitride AMB substrate and a preparation method thereof. Background Art
[0002] With the rapid development of the third generation wide bandgap semiconductors, power electronic devices are developing towards high output power and high power density, which puts forward higher performance requirements for ceramic substrate materials used in power module packaging. Silicon nitride AMB substrate has become the most promising insulating heat dissipation substrate material with its excellent comprehensive thermodynamic properties such as high strength, high toughness, high thermal conductivity and high reliability.
[0003] The difference in thermal expansion coefficient between silicon nitride ceramic and copper will cause greater stress at the copper-ceramic interface when subjected to thermal cycles, causing the ceramic to crack or the copper layer to peel off, which will lead to module failure. At present, the copper-ceramic connection method of high-reliability silicon nitride AMB substrates is mainly active metal brazing technology, among which silver-based solder paste is widely used due to its excellent wetting effect, high joint strength, good thermal conductivity and other characteristics, but it has high cost, silver electromigration risk and heavy metal pollution problems. Patent CN111403347B discloses a prefabricated silver-free solder sheet. Through the optimization design of each layer of the brazing interface, a very uniform interface structure and excellent temperature reliability are obtained, but the prefabricated solder sheet also brings about the problem of complex preparation and molding process for the solder sheet. At present, there is no high reliability report of silicon nitride AMB substrates prepared using silver-free solder paste technology, and high reliability and low-cost silver-free solder paste technology needs to be developed.
[0004] In summary, in order to solve the above problems, it is of great significance to provide a high-reliability silicon nitride AMB substrate with excellent interface structure. Summary of the invention
[0005] The object of the present invention is to provide an interface structure of a high-reliability silicon nitride AMB substrate and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing an interface structure of a high-reliability silicon nitride AMB substrate comprises the following steps:
[0008] S1: mixing metal powder and organic carrier, stirring to obtain silver-free solder paste;
[0009] S2: printing silver-free solder paste on both sides of silicon nitride ceramic, and then stacking copper sheets on the outer sides of both sides of the ceramic printed with solder paste, clamping, and obtaining a laminate of copper-solder paste-silicon nitride ceramic-solder paste-copper;
[0010] S3: vacuum brazing the stack obtained in S2 to form an interface structure between the copper sheet and the silicon nitride ceramic, thereby obtaining a high-reliability silicon nitride AMB substrate.
[0011] Among them, by regulating the elemental composition and brazing process of silver-free solder paste and structurally designing the brazing interface, the residual stress after silver-free solder paste welding can be effectively reduced and the temperature reliability of the copper clad laminate can be improved.
[0012] More optimally, the silver-free solder paste comprises the following raw materials: 80 to 90 parts of metal powder and 10 to 20 parts of organic carrier by mass.
[0013] More optimally, the metal powder comprises the following raw materials, calculated by mass fraction: 15-40% active metal, 10-30% melting point metal, and the rest is copper.
[0014] More optimally, the active metal includes one or more of zirconium, titanium, hafnium, chromium, and vanadium; and the melting point reducing metal includes one of tin and indium.
[0015] More optimally, the organic carrier includes the following raw materials, by mass fraction: 13-15% ethyl cellulose, 2-4% acrylic resin, 2-4% hydrogenated castor oil, 2-6% polyamide wax, 2-5% dioctyl phthalate, 4-7% dibutyl phthalate, and the rest is solvent.
[0016] More optimally, the solvent comprises butyl carbitol and alcohol ester dodecahydrate in a mass ratio of 1:1.
[0017] More optimally, during the vacuum brazing process: the temperature is 800-1000°C, the insulation time is 20-90 minutes, and the vacuum degree in the furnace is <0.01Pa.
[0018] More optimally, an interface structure of a high-reliability silicon nitride AMB substrate is provided, wherein the interface structure comprises a buffer layer and a reaction layer; the buffer layer contacts copper, and the reaction layer contacts silicon nitride ceramics; the thickness of the reaction layer is 0.1 to 1 μm; and the thickness of the buffer layer is 3 to 20 μm.
[0019] Among them, in the high-reliability silicon nitride AMB substrate after brazing, from the outside to the inside, they are copper layer, buffer layer, reaction layer, silicon nitride ceramic, reaction layer, buffer layer, and copper layer, and the interface structure on both sides is the same.
[0020] The reaction layer is a nitride layer of active elements and silicon nitride ceramics, the buffer layer is formed by alternating needle-shaped alloy layers and copper layers, and the buffer layer mainly contains copper, active metals and melting metals. The active metal content in the buffer layer is 40-70wt%, the copper content is 10-40wt%, the melting metal content is 0.5-5wt%, and the silicon content is 3-15wt%, and the silicon comes from the silicon nitride ceramic sheet in the reaction process.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) By adding melting point reducing metal and combining it with a specific sintering process, the brazing interface structure was regulated and the thickness of the hard and brittle nitride reaction layer was reduced to 0.1-1 μm, which greatly reduced the residual stress of the brazing and significantly improved the stability and reliability of the interface structure.
[0023] (2) During the brazing process, most of the melting metal diffuses from the metal melt into the copper during the heating and heat preservation process, avoiding the formation of hard and brittle compounds such as copper-indium or copper-tin at the brazing interface. After the brazing is completed, a special structure of needle-shaped alloy layers and copper layers interlaced is formed in the buffer layer. This special interface structure of the needle-shaped alloy layer "pinned" in the copper layer significantly improves the buffer layer's ability to buffer stress.
[0024] (3) The present invention uses a solder paste that does not contain silver to connect the silicon nitride ceramic sheet and the copper sheet, thereby avoiding the silver migration problem during use and significantly reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of stacking of silicon nitride AMB substrate in step S2 of the embodiment;
[0026] Figure 2 The copper-ceramic interface structure of the silicon nitride AMB substrate prepared in Example 1;
[0027] Figure 3 The copper-ceramic interface structure of the silicon nitride AMB substrate prepared in Example 2;
[0028] Figure 4 The copper-ceramic interface structure of the silicon nitride AMB substrate prepared in Example 3;
[0029] Figure 5 This is the interface structure of the copper-ceramic connection of the silicon nitride AMB substrate prepared in the comparative example. DETAILED DESCRIPTION
[0030] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0031] It should be noted that there is no special restriction on the purchase manufacturers of all raw materials involved in the present invention, which exemplarily include: silicon nitride ceramic sheets, provided by Japan Fine Ceramics Co., Ltd.; oxygen-free copper sheets, provided by Aurubis Company in Europe.
[0032] In the following examples, parts are by mass and all raw materials are commercially available.
[0033] Example 1: The metal powder comprises the following raw materials, by mass fraction: 20% active metal: titanium, 25% melting point metal: indium, and the rest is copper; the organic carrier comprises the following raw materials, by mass fraction: 13% ethyl cellulose, 2% acrylic resin, 4% hydrogenated castor oil, 6% polyamide wax, 3% dioctyl phthalate, 5% dibutyl phthalate, and the rest is solvent (butyl carbitol and alcohol ester dodeca in a mass ratio of 1:1).
[0034] S1: 85 parts of metal powder and 15 parts of organic vehicle are mixed and stirred to obtain a silver-free solder paste;
[0035] S2: Print the silver-free solder paste on both sides of the 0.32mm thick silicon nitride ceramic through a 200-mesh steel screen, and then stack 0.8mm thick copper sheets on the outside of the two sides of the ceramic printed with solder paste, and clamp them to obtain a copper-solder paste-silicon nitride ceramic-solder paste-copper laminate
[0036] S3: The stack obtained in S2 is transferred to a vacuum brazing furnace, and vacuum brazing is performed at 900° C. under a vacuum degree of less than 0.01 Pa, and the temperature is kept for 40 minutes to obtain a silicon nitride AMB substrate.
[0037] Example 2: The metal powder comprises the following raw materials, by mass fraction: 30% active metal: zirconium, 15% melting point metal: indium, and the rest is copper; the organic carrier comprises the following raw materials, by mass fraction: 15% ethyl cellulose, 4% acrylic resin, 3% hydrogenated castor oil, 3% polyamide wax, 3% dioctyl phthalate, 4% dibutyl phthalate, and the rest is solvent (butyl carbitol and alcohol ester dodeca in a mass ratio of 1:1).
[0038] S1: 85 parts of metal powder and 15 parts of organic vehicle are mixed and stirred to obtain a silver-free solder paste;
[0039] S2: Print the silver-free solder paste on both sides of the 0.32mm thick silicon nitride ceramic through a 200-mesh steel screen, and then stack 0.8mm thick copper sheets on the outside of the two sides of the ceramic printed with solder paste, and clamp them to obtain a copper-solder paste-silicon nitride ceramic-solder paste-copper laminate
[0040] S3: The stack obtained in S2 is transferred to a vacuum brazing furnace, and vacuum brazing is performed at 990° C. under a vacuum degree of less than 0.01 Pa, and the temperature is kept for 50 minutes to obtain a silicon nitride AMB substrate.
[0041] Example 3: In which, the metal powder includes the following raw materials, calculated by mass fraction: 15% active metal: titanium, 25% melting point metal: tin, and the rest is copper; the organic carrier includes the following raw materials, calculated by mass fraction: 13% ethyl cellulose, 2% acrylic resin, 2% hydrogenated castor oil, 2% polyamide wax, 5% dioctyl phthalate, 4% dibutyl phthalate, and the rest is solvent (butyl carbitol and alcohol ester dodeca in a mass ratio of 1:1).
[0042] S1: 85 parts of metal powder and 15 parts of organic vehicle are mixed and stirred to obtain a silver-free solder paste;
[0043] S2: Print the silver-free solder paste on both sides of the 0.32mm thick silicon nitride ceramic through a 200-mesh steel screen, and then stack 0.8mm thick copper sheets on the outside of the two sides of the ceramic printed with solder paste, and clamp them to obtain a copper-solder paste-silicon nitride ceramic-solder paste-copper laminate
[0044] S3: The stack obtained in S2 is transferred to a vacuum brazing furnace, and vacuum brazing is performed at 1000° C. under a vacuum degree of less than 0.01 Pa, and the temperature is kept for 60 minutes to obtain a silicon nitride AMB substrate.
[0045] Comparative Example 1: The present invention compares the interface structure of a silicon nitride AMB substrate made using silver-copper-titanium solder paste: wherein the metal powder comprises the following raw materials, calculated by mass fraction: 5% active metal: titanium, 28% copper, and the rest is silver; the organic carrier comprises the following raw materials, calculated by mass fraction: 13% ethyl cellulose, 2% acrylic resin, 4% hydrogenated castor oil, 6% polyamide wax, 3% dioctyl phthalate, 5% dibutyl phthalate, and the rest is a solvent (butyl carbitol and alcohol ester twelve in a mass ratio of 1:1).
[0046] S1: 85 parts of metal powder and 15 parts of organic vehicle are mixed and stirred to obtain a silver-free solder paste;
[0047] S2: Print the silver-free solder paste on both sides of the 0.32mm thick silicon nitride ceramic through a 200-mesh steel screen, and then stack 0.8mm thick copper sheets on the outside of the two sides of the ceramic printed with solder paste, and clamp them to obtain a copper-solder paste-silicon nitride ceramic-solder paste-copper laminate
[0048] S3: The stack obtained in S2 is transferred to a vacuum brazing furnace, and vacuum brazing is performed at 890° C. under a vacuum degree of less than 0.01 Pa, and the temperature is kept for 60 minutes to obtain a silicon nitride AMB substrate.
[0049] Performance test: Examples 1, 2, 3 and the comparative example were subjected to temperature reliability test. The temperature reliability test was conducted by a water-cooling shock method, as follows: the heating platform was heated to 350°C and kept at a constant temperature. The product was placed on the heating platform and kept warm for 2 minutes. The product was then quickly scraped into room temperature water with a scraper. This was one cycle. After each cycle, an ultrasonic scan was performed to observe whether there was any failure. The number of water-cooling shocks at the beginning of failure was recorded for comparison. The experimental data, measured by the number of water-cooling shocks, are shown in Table 1.
[0050] Table 1
[0051] project Water cooling shock times Example 1 50 Example 2 35 Example 3 30 Comparative Example 1 20
[0052] Conclusion: As shown in Table 1, the performance of the silicon nitride AMB substrate prepared in the embodiment and the comparative example is significantly different. The present invention significantly improves its stress buffering capacity by adjusting the element composition and brazing process of the silver-free solder paste and designing the structure of the welding interface, thereby achieving the purpose of significantly improving the temperature reliability of the silicon nitride AMB substrate. Figure 2 , i.e., the interface structure of the copper-ceramic connection of the silicon nitride AMB substrate prepared in Example 1. It can be clearly seen that the interface is composed of a copper layer, a buffer layer, a reaction layer, and a silicon nitride ceramic from top to bottom. The interfaces of the layers are relatively uniform and flat. The buffer layer is a uniform and dense needle-shaped alloy, which is "pinned" in the copper layer. It is this special interface structure that significantly improves the buffering capacity of the buffer layer to stress. Figure 5 In the copper-ceramic interface structure of the silicon nitride AMB substrate prepared in Comparative Example 1, it can be clearly seen that the interface is uneven, especially on the upper copper side, which reduces the uniformity of brazing and easily forms stress concentration points, reducing the ability to buffer stress. In addition, there are uneven copper metal particles in the form of dots or strips inside the alloy connected at the interface. These unevenly distributed silver-copper eutectic structures have poor stress buffering capabilities and low temperature reliability.
[0053] In summary, the present invention successfully obtains an interface structure of a high-reliability silicon nitride AMB substrate by adding a melting-reducing metal to a silver-free solder paste and combining it with a specific sintering process, which has a good effect on stress buffering and has high temperature reliability.
[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an interface structure of a high-reliability silicon nitride AMB substrate, characterized in that: The following steps are involved: S1: mixing metal powder and organic carrier, stirring to obtain silver-free solder paste; S2: printing silver-free solder paste on both sides of silicon nitride ceramic, and then stacking copper sheets on the outer sides of both sides of the ceramic printed with solder paste, clamping, and obtaining a laminate of copper-solder paste-silicon nitride ceramic-solder paste-copper; S3: vacuum brazing the stack obtained in S2 to form an interface structure between the copper sheet and the silicon nitride ceramic, thereby obtaining a high-reliability silicon nitride AMB substrate.
2. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 1, characterized in that: The silver-free solder paste comprises the following raw materials: 80 to 90 parts of metal powder and 10 to 20 parts of organic carrier by weight.
3. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 1, characterized in that: The metal powder comprises the following raw materials, calculated by mass fraction: 15-40% active metal, 10-30% melting point metal, and the rest is copper.
4. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 3, characterized in that: The active metal includes one or more of zirconium, titanium, hafnium, chromium and vanadium; the melting point reducing metal includes one of tin and indium.
5. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 1, characterized in that: The organic carrier comprises the following raw materials, calculated by mass fraction: 13-15% ethyl cellulose, 2-4% acrylic resin, 2-4% hydrogenated castor oil, 2-6% polyamide wax, 2-5% dioctyl phthalate, 4-7% dibutyl phthalate, and the rest is solvent.
6. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 5, characterized in that: The solvent includes butyl carbitol and alcohol ester dodecaol in a mass ratio of 1:
1.
7. The method for preparing an interface structure of a high-reliability silicon nitride AMB substrate according to claim 1, characterized in that: During the vacuum brazing process: the temperature is 800-1000°C, the insulation time is 20-90 minutes, and the vacuum degree in the furnace is less than 0.01Pa.
8. An interface structure of a high-reliability silicon nitride AMB substrate, characterized in that: The invention is prepared by the method for preparing the interface structure of a high-reliability silicon nitride AMB substrate as claimed in any one of claims 1 to 7.
9. The interface structure of a high-reliability silicon nitride AMB substrate according to claim 8, characterized in that: The interface structure comprises a buffer layer and a reaction layer; the buffer layer contacts copper, and the reaction layer contacts silicon nitride ceramics; the thickness of the reaction layer is 0.1 to 1 μm; and the thickness of the buffer layer is 3 to 20 μm.
Citation Information
Patent Citations
A copper-ceramic interface structure for a high-reliability silicon nitride copper-clad ceramic substrate and its preparation method
CN111403347B
Copper-ceramic interface structure of high-reliability silicon nitride copper-coated ceramic substrate and preparation method of copper-ceramic interface structure
CN111403347A
Heat-not-burn electronic cigarette ceramic heating sheet and preparation method thereof
CN114947225A
AMB silicon nitride ceramic copper-coated sheet and preparation method thereof
CN116133269A
Ceramic copper-clad plate as well as preparation method and application thereof
CN117769152A